Measuring cosmic density of neutral hydrogen via stacking the DINGO-VLA data. Issue 2 (2nd October 2021) - Chen, Qingxiang; Meyer, Martin; Popping, Attila; Staveley-Smith, Lister; Bryant, Julia; Delhaize, Jacinta; Holwerda, B W; Cluver, M E; Loveday, J; Lopez-Sanchez, Angel R; Zwaan, Martin; Taylor, E N; et al.
ABSTRACT: We use the 21-cm emission-line data from the Deep Investigation of Neutral Gas Origin-Very Large Array (DINGO-VLA) project to study the atomic hydrogen gas H i of the Universe at redshifts z < 0.1. Results are obtained using a stacking analysis, combining the H i signals from 3622 galaxies extracted from 267 VLA pointings in the G09 field of the Galaxy and Mass Assembly Survey (GAMA). Rather than using a traditional one-dimensional spectral stacking method, a three-dimensional cubelet stacking method is used to enable deconvolution and the accurate recovery of average galaxy fluxes from this high-resolution interferometric data set. By probing down to galactic scales, this experiment also overcomes confusion corrections that have been necessary to include in previous single-dish studies. After stacking and deconvolution, we obtain a 30σ H i mass measurement from the stacked spectrum, indicating an average H i mass of ${\rm{M_{\rm{H\, \small{I}}}}}=(1.67± 0.18)× 10^{9}~{\rm{{\rm M}_{\odot }}}$ . The corresponding cosmic density of neutral atomic hydrogen is ${\rm{Ω _{\rm{H\, \small{I}}}}}=(0.38± 0.04)× 10^{-3}$ at redshift of z = 0.051. These values are in good agreement with earlier results, implying there is no significant evolution of $Ω _{\rm{H\, \small{I}}}$ at lower redshifts.